Práticas integrativas e complementares no sistema único de saúde brasileiro - Jane Saula de Oliveira (2019)
The general objective of this dissertation was to evaluate the offer of Integrative and Complementary Practices in Health in the Brazilian Unified Health System, through two studies. Study 1 had the objective of evaluating the frequency of provision of Integrative and Complementary Practices in Health (ICPH) by the Basic Attention Teams (BAT) in the Brazilian public health service and its association with the work and management process of the BAT and with the existence of PICS policies at the state level of management of the Unified Health System (UHS). While Study 2 aims to describe the implantation process and the current situation of the Homeopathy, Acupuncture and Anthroposophic Medicine Program (Programa de Homeopatia, Acupuntura e Medicina Antroposófica PRHOAMA) in the Belo Horizonte city, Minas Gerais. Study 1, with a national base, was carried out with secondary public data (Programa de Melhoria do Acesso e Qualidade da Atenção Básica - PMAQ-AB, 2nd cycle, IBGE and DATASUS) and research by official data from Federal Units (FD). The analyzed data presented a multilevel structure, being: level 1: BAT and level 2: FD. The dependent variable was the provision of ICPS by the BAT, and the independent level 1 referred to the work process and management of the teams, and in level 2, the existence of a State Policy on Integrative and Complementary Practices (SPICP). In Study 2, a documentary research was carried out both in the institutional archives of PRHOAMA, in the headquarters of the Municipal Health Department, and through the internet, in search of official documents (DOM, ordinances, resolutions), pamphlets, posters, protocols, presentations, reports and newspaper news. As results of Study 1, it is observed that the ICPH were offered by 19% of the 29,778 BAT participants of the PMAQ-AB. There was a higher proportion of PICs offered by BAT that presented better work process and management characteristics, in accordance with the principles of Primary Health Care; and in the UF that had SPICP and more professionals registered in ICPH. With Study 2, it was possible to verify that the initiative for the regulation of ICPH in the public health services of BH began in 1990 and since then the Program has been established, working especially in the matrix support of the BAT and the Núcleos de Apoio à Saúde da Família/AB (NASF/AB). It is concluded that, at the national level, the supply of ICPH is associated with both the characteristics of the BAT and the initiatives at the FU level, such as own policies and human resources in the ICPH area. In addition, PRHOAMA is one of the most significant pioneering experiences in the implementation of ICPH in UHS at the municipal level.